Analysis of The Effect of Total Quality Management on Organizational Performance in Small and Medium Enterprises with Innovation Process Speed as a Mediating Variable in SMES in the Culinary Sector in Bogor City - Andini Sih Afsari Utami; Unggul Purwohedi; Rida Prihatni (Journal of World Science, 2024)
The increasing competitiveness of the business environment, especially in the culinary industry, has encouraged small and medium-sized enterprises to focus on improving their organizational performance. This study aims to determine and analyze the effect of total quality management on organizational performance in small and medium enterprises with the speed of the innovation process as a mediating variable in culinary SMEs in Bogor City. The method used in this research is quantitative. The population in this study were 100 respondents of culinary SMEs in Bogor City. This study uses purposive sampling technique to determine the sample. Based on the results showed that TQM significantly has a positive influence on organizational performance, TQM significantly has a positive influence on the speed of the innovation process, the speed of the innovation process significantly has a positive influence on organizational performance, and there is a positive relationship and influence between Total Quality Management and organizational performance mediated by the speed of the innovation process. The results of this study provide implications for SMEs regarding the application of Total Quality Management. SMEs are expected to focus on services and products that meet consumer demand, reduce production costs, and offer affordable prices without sacrificing quality, thereby increasing consumer loyalty and business competitiveness. This research has implications for the need for SMEs to invest in training and development of effective TQM systems and pay attention to market dynamics to continue to innovate and meet consumer expectations.